Polymer-directed synthesis of metal oxide-containing nanomaterials for electrochemical energy storage - Mai, Yiyong; Zhang, Fan; Feng, Xinliang (Nanoscale, 2014)
Metal oxide-containing nanomaterials (MOCNMs) of controllable structures at the nano-scale have attracted considerable interest because of their great potential applications in electrochemical energy storage devices, such as lithium-ion batteries (LIBs) and supercapacitors. Among many structure-directing agents, polymers and macromolecules, including block copolymers (BCPs) and graphene, exhibit distinct advantages in the template-assisted synthesis of MOCNMs. In this feature article, we introduce the controlled preparation of MOCNMs employing BCPs and graphene as structure-directing agents. Typical synthetic strategies are presented for the control of structures and sizes as well as the improvement of physical properties and electrochemical performance of MOCNMs in LIBs and supercapacitors. © 2014 The Royal Society of Chemistry.
CRIS-Team Scopus Importer:2023-03-20